Seismic waveform inversion as a method for time-lapse monitoring at CO2 geological storage sites - A synthetic study - Zhang, F.; Juhlin, Christopher (Society of Petroleum Engineers, 2011)
Injection of CO2 into reservoirs will increase the pressure in the reservoir and lower the seismic velocity of the reservoir formation. Time-lapse 3D surface seismic surveys are a proven reservoir monitoring tool. As an alternative, we investigate here the use of a limited number of low frequency sources and broadband receivers for detecting changes in the subsurface response of the site. We do this by generating synthetic data over layered media, before and after CO2 injection based on the geological information from the CO2SINK site at Ketzin, west of Berlin. Rather than using conventional CDP processing, we investigate if seismic waveform tomography can be used for time-lapse monitoring of the subsurface.